2019
DOI: 10.1111/srt.12725
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on ultrasound techniques applied to cicatricial alopecia

Abstract: Background: Cicatricial alopecia (CA) is a group of disorder characterized by permanent destruction of the hair follicle. Shear wave elastography (SWE) and superb microvascular imaging (SMI) are noninvasive ultrasonic techniques which evaluate thickness, stiffness, and vascular index of tissues.Objectives: This study explored the ranges of cicatricial alopecia area and normal scalp with a combined modality of SMI and SWE and investigated the feasibility of their use in assessing these diseases.Methods: Sevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…4 Our experience shows that the use of SMI with high-frequency ultrasound is convenient because it allows better evaluation of slow blood flow than do commonly used methods such as PDI and CDI. 17,18 After the article by Kaya İslamoğlu et al, 21 this work is the second to describe the use of SMI in dermatology. Additional studies of such applications of SMI and high-frequency ultrasound are required to elucidate the use of this new technology to aid diagnostic skin assessment.…”
Section: Mhz Probe and Superb Microvascular Imaging (Smi)mentioning
confidence: 95%
“…4 Our experience shows that the use of SMI with high-frequency ultrasound is convenient because it allows better evaluation of slow blood flow than do commonly used methods such as PDI and CDI. 17,18 After the article by Kaya İslamoğlu et al, 21 this work is the second to describe the use of SMI in dermatology. Additional studies of such applications of SMI and high-frequency ultrasound are required to elucidate the use of this new technology to aid diagnostic skin assessment.…”
Section: Mhz Probe and Superb Microvascular Imaging (Smi)mentioning
confidence: 95%
“…Govind and coworkers found that SMI is more sensitive than color Doppler in demonstrating microvenous reflux in limbs with venous disease and SMI 30 . İslamoğlu and Uysal employed SMI to assess plaques of cicatricial alopecia 31 . To our knowledge, no study has investigated yet the value of SMI in studying skin vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Este método combinado perceberia precocemente alterações na elasticidade do couro cabeludo, reflectindo o grau de inflamação. 27…”
Section: Discussionunclassified